Lipid metabolism disruption as a conserved early response to Benzophenone-1: Pathway sensitivity profiling via dose-dependent yeast functional genomics platform - Xinyuan Xu; Shasha Zhang; Dake Cao; Linhao Zong; Dong Chen; Ying Peng; Ping Jin; Fei Ma; Xiaowei Zhang; Miao Guan (Environmental Pollution, 2026)

Innovative hybrid anaerobic ammonium oxidation system enhances nitrogen and sulfur elimination in landfill leachate treatment - Lina Wu; Yufan Liu; Yinghao Tian; Jiayuan Xu; Jianda Xu; Chenxu Wang; Linhao Zhang; Mengqi He; Zhi Jiao; Yongzhen Peng (Bioresource Technology, 2025)

Construction of island ecological security pattern under multi-circle development pattern: Evidence from Hainan Island - Sizheng Li; Feng Gui; Hongyu Li; Yanwei Song; Linhao Peng; Lin Zhou; Yang Wang (Ocean & Coastal Management, 2025)

Deciphering early molecular responses to benzotriazole ultraviolet stabilizers-induced toxicity using a dose-dependent yeast functional genomics approach - Xinyuan Xu; Linhao Zong; Shasha Zhang; Dake Cao; Ziqi Tang; Dong Chen; Ying Peng; Luhang She; Ping Jin; Xiaowei Zhang; Miao Guan (Environmental Pollution, 2025)

Effects of NGF-chitosan on alleviating secondary degeneration and repairing primary degeneration after expanded partial optic nerve transection - Xiao Liu; Hongmei Duan; Limin Gao; Linhao Yuan; Peng Hao; Wen Zhao; Yudan Gao; Zitian Huang; Xi Wang; Wenjianlong Zhou; Shunchang Ma; Ningli Wang; et al. (Science China Life Sciences, 2025)

Enhancement of simultaneous partial nitrification anammox and denitrification nitrogen removal and biofilm formation by novel biochar/nano zerovalent iron modified polyurethane biocarrier for treatment of landfill leachate - Lina Wu; Yinghao Tian; Yufan Liu; Jianda Xu; Chenxu Wang; Linhao Zhang; Mengqi He; Yongzhen Peng (Chemical Engineering Journal, 2025)

Negative carbon emission power generator: A combination of high temperature proton exchange membrane fuel cell and absorption carbon capture system - Chaohuan Tan; Linhao Cheng; Wanli Peng; Hanxin Yang; Rongxiang Luo; Juncheng Guo (Journal of Cleaner Production, 2025)

Synergy between Fenton reagent and solid waste-based solidifying agents during the solidification/stabilization of lead(II) and arsenic(III) contaminated soils - Tao Chen; Bin He; Dongxin Chu; Linhao Wang; Xiaochuang Peng; Xiaoqing Nie; Fuli Ma; Pengju Han; Xiaohong Bai (Journal of Environmental Management, 2024)

Three birds with one stone: A nano zeolitic imidazolate framework-luciferase-antimicrobial peptide biocomposite-based biosensing platform for improving enzyme stability, detection sensitivity, and sterilization effect - Renjie Zhou; Tingting He; Linhao Peng; Dengfeng Li; Zhenzhong Yu; Xin Yang; Ning Gan (Chemical Engineering Journal, 2024)

Study on the solidification/stabilization of cadmium-contaminated soil by red mud-assisted blast furnace slag under excitation conditions - Tao Chen; Linhao Wang; Bin He; Xiaochuang Peng; Xiaoqing Nie; Fuli Ma; Pengju Han; Xiaohong Bai (Journal of Cleaner Production, 2024)

Torsional Optical Fiber Stress Analysis and Vortex-Induced Vibration Study of Three-Core Submarine Cable - Haotian Tan; Yanpeng Hao; Peng Zhang; Qishun Li; Wanxing Tian; Linhao Chen; Lin Yang; Licheng Li (Journal of Marine Science and Engineering, 2023)
Due to current scouring, submarine cables are prone to be exposed, suspended, and even vortex-induced vibration, which is not conducive to the safe operation of the power grid. In this contribution, the finite element simulation model of a 35 kV three-core optical fiber composite submarine cable with a suspended span length of 9.5 m is established. The natural frequency of the model is obtained through modal analysis. Then the vortex-induced vibration is simulated by the fluid–structure coupling method, and the stress distribution and change law of the torsional optical fiber is extracted. The results show that in the submarine cable, there appears to be a beating vibration and locking phenomena respectively, under two flow velocities. The transverse vibration amplitude of the latter increases significantly due to a resonance state. When the flow direction is perpendicular to the submarine cable, the stress distribution of the torsional optical fiber at the initial moment and at the 1/2 T moment of a vibration cycle approximately represents a mirror image relationship. In addition, the frequency of the stress change is the same as the frequency of the vortex-induced vibration, which can judge whether the vortex-induced vibration occurs. Moreover, the vortex-induced vibration range can be determined by the maximum stress change location.

Intensified lacustrine turbidite deposition as a response to the Carnian Pluvial Episode: Insights from the Triassic Ordos Basin in North China Plate - Peng Chen; Benzhong Xian; Meijun Li; Linhao Fang; Naveed Ur Rahman; Jianping Liu; Sirui Chen; Rongheng Tian; Qianran Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Numerical Study of the Local Scouring Process and Influencing Factors of Semi-Exposed Submarine Cables - Qishun Li; Yanpeng Hao; Peng Zhang; Haotian Tan; Wanxing Tian; Linhao Chen; Lin Yang (Journal of Marine Science and Engineering, 2023)
Local scouring might result in the spanning of submarine cables, endangering their mechanical and electrical properties. In this contribution, a three-dimensional computational fluid dynamics simulation model is developed using FLOW-3D, and the scouring process of semi-exposed submarine cables is investigated. The effects of the sediment critical Shields number, sediment density, and ocean current velocity on local scouring are discussed, and variation rules for the submarine cables’ spanning time are provided. The results indicate that three scouring holes are formed around the submarine cables. The location of the bottom of the holes corresponds to that of the maximum shear velocity. The continuous development of scouring holes at the wake position leads to the spanning of the submarine cables. The increase in the sediment’s critical Shields number and sediment density, as well as the decrease in the ocean current velocity, will extend the time for maintaining the stability of the upstream scouring hole and retard the development velocity of the wake position and downstream scouring holes. The spanning time has a cubic relationship with the sediment’s critical Shields number, a linear relationship with the sediment density, and an exponential relationship with the ocean current velocity. In this paper, the local scouring process of semi-exposed submarine cables is studied, which provides a theoretical basis for the operation and maintenance of submarine cables.

Seasonal predictable source of the East Asian summer monsoon rainfall in addition to the ENSO–AO - Kairan Ying; Dabang Jiang; Xiaogu Zheng; Carsten S. Frederiksen; Jing Peng; Tianbao Zhao; Linhao Zhong (Climate Dynamics, 2023)

Morphology and ontogeny of the eodiscoid trilobite Pagetia vinusta from the Cambrian (Miaolingian) of South China - Linhao Cui; Tao Dai; Xingliang Zhang; Shanchi Peng (PalZ, 2019)